Chloramphenicol Loaded Microemulsions: Development, Characterization and Stability - Rashid, Muhammad Abid; Naza, Tehreem; Abbas, Madeeha; Nazir, Sadia; Younas, Nafisa; Majeed, Sana; Qureshi, Naseem; Akhtar, Muhammad Nadeem (Elsevier, 2019)
This study aimed to formulate and characterize microemulsions containing chloramphenicol. Microemulsions represent highly biocompatible drug delivery systems due to their potential for increased absorption as well as high solubilization capacity. MEs were composed of Oleic acid, non-ionic surfactants tween 20/60, 1-propanol and phosphate buffer. The optimum weight ratios of components and MEs areas were determined by pseudo-ternary phase diagram. All formulations were physically characterized by centrifugation, pH, refractive index, conductivity, viscosity, surface tension and partition coefficient. The specific residence site of chloramphenicol was detected by 1H NMR study. It was uncovered that drug is entrapped between the oxyethylene groups of hydrophilic shell of MEs. So, the drug was screened from bulk water and its stability was enhanced. Thus, all characterizations have suggested that formulated MEs have potential for ocular application, being able to use as efficient drug carrier for ocular drug delivery.